Efikasi Kombinasi Herbisida Metil Metsulfuron dan Asam Asetat pada Lahan Perkebunan Kelapa Sawit (Elaeis gueenensis Jacq.) Menghasilkan - Arbania, Iis Okta; Sudirman, Albertus; Sari, Sismita; Syofian, Mirodi (Politeknik Negeri Lampung, 2021)
One of the obstacles that resulted in a decrease in palm oil production was the presence of weeds. Weed control needs to be done to suppress weed growth. A mixture of methyl metsulfuron herbicide and acetic acid herbicide can be used to control weeds. This research was conducted in Politeknik Negeri Lampung’s Teaching Farm. This study used a factorial randomized block design with two factors, and each treatment combination was repeated three times. The first factor is the methyl metsulfuron herbicide 20% with 3 level doses: 0 g.ha-1, 45 g,ha-1, and 75 g.ha-1 and the second factor is acetic acid herbicide 20% with 3 level doses: 0 ml.ha-1, 225 l.ha-1, and 315 l.ha-1. The result showed that the combination of methyl metsulfuron herbicide 75 g.ha-1 and acetic acid herbicide 315 l.ha-1 effective reduce weed dry weight up to 5.50 grams at 5 WAA and reduce weed cover percentage to 8% at 6 WAA. The dominant weeds that arises after the application of the methyl metsulfuron herbicide and acetic acid is Asystasia gangetica, Paspalum conjugatum, Panicum dichotomiflorum, Stachytarpeta indica, and Imperata cylindrica.